2010
DOI: 10.1093/ndt/gfq588
|View full text |Cite
|
Sign up to set email alerts
|

Relations between malnutrition-inflammation-atherosclerosis and volume status. The usefulness of bioimpedance analysis in peritoneal dialysis patients

Abstract: FO defined by m-BIA is significantly correlated with markers of malnutrition, inflammation and atherosclerosis in PD patients. The indices obtained from m-BIA, especially ECW/height, correlated well with volume overload as assessed by echocardiography and might be a measure worth testing in a properly designed clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 35 publications
7
78
0
6
Order By: Relevance
“…The inflammatory process is a well-known condition related to tissue injury and Data described as mean ± standard deviation for parametric variables or median (interquartile range) for non-parametric variables consequently cell membrane integrity disarrangement [26], and several studies with different clinical conditions also reported associations between PhA values and inflammatory markers [27][28][29]. Interestingly, adipose tissue seems to be the greatest target for leukocyte infiltration and also a source of inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) [30].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory process is a well-known condition related to tissue injury and Data described as mean ± standard deviation for parametric variables or median (interquartile range) for non-parametric variables consequently cell membrane integrity disarrangement [26], and several studies with different clinical conditions also reported associations between PhA values and inflammatory markers [27][28][29]. Interestingly, adipose tissue seems to be the greatest target for leukocyte infiltration and also a source of inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) [30].…”
Section: Discussionmentioning
confidence: 99%
“…The values of R/H, Xc/H and phase angle in our study were very similar to those described by Koh et al (26) in a group of Malaysian patients, which seems to indicate that the electrical characteristics and, therefore, body composition of this group of patients are similar. However, Demirci et al (27) in Turkish population, as well as Di-Gioia (22) in Spanish patients, found slightly higher phase angles, which could be due to better nutrition and hydration status. In spite of this, it is important to note that in all the mentioned populations, phase angles are less than 6°, a cut-off point suggested for patients on peritoneal dialysis, which is related to lower mortality (28).…”
Section: Discussionmentioning
confidence: 91%
“…9 Clinical measurements related to malnutrition, inflammation, and atherosclerosis (e.g., serum albumin, C-reactive protein [CRP], and carotid intima media thickness) were associated with symptoms of volume overload, as detected by echocardiography and bioimpedance analyses in a study of 95 PD patients. 10 Pro-brain natriuretic peptide, an indicator of volume overload, is correlated with troponin T, homocysteine, and CRP levels and malnutrition inflammation scores in patients undergoing HD. 30 These findings are important, as they indicate an association between hypervolemia and malnutrition.…”
Section: Discussionmentioning
confidence: 98%
“…8 Malnutrition is closely related with volume overload in patients with end stage renal disease. 9,10 We previously reported that hypervolemic cardiovascular markers (increased left atrial volume and decreased vena cava inferior collapsibility index) and LVH (increased left ventricular mass index) were associated with deterioration of nutritional status in HD patients. 11 Hypervolemia is considered as the main causative factor for increased blood pressures at nighttime.…”
Section: Introductionmentioning
confidence: 99%